MAPPING OF POTENTIAL AGRICULTURE IN THE DEVELOPMENT OF PRIORITY AGROINDUSTRY IN KEPULAUAN MERANTY REGENCY - Septina Elida (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2017)
The agricultural sector has an important role for rural communities in moving its economy. Therefore, that agricultural potential should be utilized as much as possible for socialwelfare. This study aimed to analyze the potential of agricultural commodities and priority of the factors that determine superioragroindustrybased potensial of agricultural commodities. This study usedsurvey, which was conduct in the Meranti IslandsDistrict from January to May 2016.Respondents involving stakeholders from experts, government agencies and community leaders. The analysis was the Hirarchi Analytical Process (AHP). The results showedthat the potential of agricultural commodities which was develope in Meranti Islands District were sago, coconut and rubber. Determinants: 1) Natural resources (climate, rainfall and land suitability), the priority factor were the land suitability and climate. 2) Human resources (formal education and skills), the priority factor was skill, 3) capital (land, seeds, tools, technology, and ease of cultivation), the priority factor were land, seeds, ease of cultivation. 4) Socio-economic and cultural (ethnic, contribution to GDP), the priority factor was the contribution to the GDP.Superior agroindustriesthat has be developed in the District of Meranti Islands based agricultural potential was agroindustrial sago and coconut. Determinants: 1). The technical aspects (raw materials, capital, technology and infrastructure), the priority factor were the raw material and capital. 2) Economical aspects (price, market, downstream prospects, and the contribution to the GDP), the priority factor are market and downstream prospects. 3) Socio-economic and cultural aspects (education and labor absorption), the priority factor in Agroindustry sago was education, whereas in the palm agro-industry was labor absorption.